COMPARISON OF DYADIC METHOD STRUCTURE AND LITTLE METHOD WITH BRAIN GYM COMBINATION ON THE ACTIVITIES AND LEARNING RESULTS OF CLASS VII STUDENTS OF SMP NEGERI 8 YOGYAKARTA - Eka Triyani (Universitas Ahmad Dahlan, 2017)
The population in this study were eighth-grade students of SMP Negeri 8 Yogyakarta in the 2015/2016 academic year consisting of 5 classes. With the random sampling technique, class VII I was selected as the Structure Dyadic Method experimental class and class VII F as the Brain Gym experimental class. The design in this study uses factorial design. Data collection techniques using questionnaires and test methods. Questionnaire sheets are used to determine the level of student activity, while multiple-choice questions are used to find out the results of learning mathematics. The data collection instrument test uses a validity test and a reliability test. The data analysis technique used is the prerequisite test, normality test, homogeneity test, and hypothesis testing. The results of the experimental class hypothesis test with a significant level of 5% and dk = 62 indicate that: (1) there is a difference inactiveness in learning using the Structure Dyadic Method and lecture method with a combination of Brain Gym shown by , so that (2) there are differences in learning outcomes using the Dyadic Method Structure and lecture methods with a combination of Brain Gym shown by , so that > (3) Structure Dyadic Method learning is better than learning lecture method with a combination of Brain Gym to the activeness and student learning outcomes, this is indicated by the activeness using the Dyadic Method Structure 2,119216 and , so that and learning outcomes using the Dyadic Method Structure and , so that .